Seed morphology characterization and salinity effects on two popular rice (Oryza sativa L.) varieties of Nagaland - Zenwang Konyak; Therila; Keneizoulhou Kesiezie (ORYZA-An International Journal of Rice, 2024)
Salinity is one of the significant problems in rice production as it limits its growth and development. Salinity can occur through natural processes due to weathering and human intervention, such as irrigation. The present study reports two different rice varieties, 'Makrilha' and 'Thevur' which are categorized as very long (< 7.50 mm) and slender in shape (< 3.0 mm) and subjected to different salt treatments (0 mM, 100 mM, 200 mM, and 300 mM NaCl solutions) and their germination responses, such as germination percentage (GP), germination index (GI), mean germination time (MGT), vigor index (VI), root and shoot length. The study concluded that Makrilha has a higher GP (88.33%) as compared to Thevur (63%) at 200 mM NaCl solution. Both the rice showed 100% germination in the control 0 mM and 100 mM salt solutions, and no germination was recorded in the 300 mM NaCl solution. GI was recorded at its maximum in Makrilha as compared to Thevur. MGT and VI were more concentrated in Thevur than Makrilha. There was a significant difference in GI, VI, root, and shoot length (P < 0.05) as salinity increased for both rices. There was no significant difference in GP (P = 0.122) and MGT (P = 0.088). The study also found a positive correlation between GI and GP. MGT is negatively correlated with GP and GI. VI is positively correlated with GP, and GI is negatively correlated with MGT. Root and shoot length are positively correlated with GP, GI, and VI but negatively correlated with MGT for both rice varieties. The rice root and shoot length are affected as salt concentration increases and are statistically significant (root P = 0.012, shoot P = 0.001). Salt is used to control weeds in almost every part of Nagaland. Thus, the effect of salt applications needs to be studied in rice. Based on the data obtained for germination parameters such as GP, GI, VI, MGT, root and shoot length, 'Makrilha' tends to show more tolerance towards salinity as compared to 'Thevur' under controlled environmental conditions.  Thus, this study can provide insight into selecting rice with a higher salt tolerance for cultivation.